Thiazolidinediones play a positive role in the vascular endothelium and inhibit plaque progression in diabetic patients with coronary atherosclerosis: A systematic review and meta-analysis - Xue, Cheng Yuan; Zhou, Meng Qi; Zheng, Qi Yan; Zhang, Jin Hui; Cheng, Wei Ting; Bai, Xue Hui; Zhou, Fen; Wu, Ai Ming; Nie, Bo; Liu, Wei Jing; Lou, Li Xia (Frontiers in Cardiovascular Medicine, 2022)
Rosiglitazone (Avandia) and pioglitazone (Actos) belong to the class of thiazolidinediones (TZDs) drugs that act by increasing insulin sensitivity and are widely used for treating diabetic patients with insulin resistance. TZDs exhibit anti-inflammatory and antioxidant properties, then may play an active role in inhibiting plaque formation and coronary atherosclerosis. But the results of evidence-based medicine suggest that TZDs may increase the risk of cardiovascular adverse events. To explore the dispute in depth, our meta-analysis aimed to evaluate the changes in vascular endothelial and plaque-related indicators followed treatment with TZDs in diabetic patients with coronary atherosclerosis. According to our meta-analysis, TZDs showed an inhibiting effect on plaque progression and a protective effect on the vascular endothelium in patients with diabetes and coronary atherosclerosis. Interestingly, these effects may not depend on regulation of inflammation and lipid metabolism. By this token, TZDs may develop a potential protective effect on myocardial infarction.